Tolerance to reinforcer delay as a behavioral cusp precursor to selfcontrol (Brazilian Journal of Behavioral and Cognitive Therapy, 2018)
The theoretical assumptions of Behavior Analysis and the empirical literature have both linked tolerance to reinforcer delay to self-control. However, a developmental perspective about its relevance has not yet been explored. The present study analyzed the tolerance to reinforcer delay as a possible behavioral cusp precursor to self-control. For this analysis we used texts by Skinner and other behavior analysts that discuss the constructs of self-control, human development and behavioral cusp, as well as empirical articles examining the relationships between tolerance to reinforcer delay and self-control. In addition, developmental contingencies, which may favor the tolerance to reinforce delay were discussed. It is concluded that the tolerance to reinforcer delay meets all criteria established to be considered a behavioral cusp and that, in this sense, should constitute an important target of intervention in childhood, aiming at the future development of self-control.
Keywords: self-control; tolerance to reinforcer delay; behavioral cusp